Prenatal Tobacco Exposure and Childhood Neurodevelopment among Infants Born Prematurely - Robbins, Lindsay S.; Blanchard, Christina T.; Sinkey, Rachel G.; Harris, Stacy L.; Tita, Alan T.; Harper, Lorie M. (American Journal of Perinatology, 2020)
Objective Nicotine is an established neuroteratogen, and prenatal tobacco exposure alters the structure of the developing nervous system. An association between prenatal tobacco exposure and impaired neurologic function is less well established. We examine the association between prenatal tobacco exposure and childhood neurodevelopment among infants born preterm.Study Design Secondary analysis of a multicenter randomized controlled trial assessing the benefits of magnesium sulfate for the prevention of cerebral palsy in preterm infants. Women were included if they delivered a singleton and nonanomalous infant before 37 weeks. Exposure was any self-reported prenatal tobacco use. Primary outcome was the original trial composite outcome of moderate or severe cerebral palsy at 2 years of age, or stillbirth, or infant death by 1 year of age. Secondary outcomes included components of the composite and mild cerebral palsy at 2 years, Bayley Scales of Infant Development II motor and mental scores, death before two years, and use of auditory aids or corrective lenses. Multivariable logistic regression models were performed to estimate adjusted odds ratios (aOR) with 95% confidence intervals.Results Of 1,826 women included, 503 (27.5%) used tobacco. Tobacco users were more likely to be older, unmarried, and white; have a prior preterm birth; have received no prenatal care; and to use illicit drugs or alcohol. Gestational age at delivery, betamethasone exposure, and magnesium exposure were not different between groups. There were no differences in the composite primary outcome or in rates of cerebral palsy by tobacco use. Moderate developmental delay was more common among tobacco exposed in bivariate but not adjusted analysis (20.5 vs. 15.9%, p = 0.035). In adjusted analysis, tobacco exposure was associated with increased use of corrective lenses (5.0 vs. 2.9%, aOR: 2.28, 95% confidence interval: 1.28–4.07).Conclusion Prenatal tobacco exposure is not associated with neurodevelopmental impairment in infants born preterm. However, tobacco exposure may be associated with impaired vision.Key Points
Keywords: development; pregnancy; smoking; nicotine; preterm